Non-volatile CBRAM/MIM switching technology for electronically reconfigurable passive microwave devices - Purushothama, Jayakrishnan Methapettyparambu; Perret, Etienne; Vena, Arnaud (ISTE, Ltd. ; Wiley, 2022)
This book presents the applications of non-volatile CBRAM/MIM switching technology for electronically reconfigurable passive RF and microwave devices, together with theory and methods for application in rewritable chipless RFID tags. Conductive Bridging Random Access Memory (CBRAM) is a renowned and commercially used non-volatile memory concept. Having evolved over the past few decades, it is currently identified as an efficient non-volatile RF switching technology. This book presents recent research on this topic, focusing on the development of a new generation of low-cost non-volatile RF switches and their applications, demonstrating both high performance and flexibility of implementation. It includes the experimental realization of various prototypes of RF and microwave devices utilizing this technology, along with relevant analysis of mathematical and electrical models, and detailed discussions of future aspects. All devices presented are compatible with mass industrial production at an economically efficient budget through optimized fabrication steps, without the requirement of sophisticated "clean room" processes among them.